STUDI HUBUNGAN PEMERINTAH DESA DENGAN BADAN PERMUSYAWARATAN DESA DALAM PEMBUATAN PERATURAN DESA DI DESA KONANG, KECAMATAN GLAGAH, KABUPATEN LAMONGAN - Adi Rivanto, M. Zulham (JPAP: Jurnal Penelitian Administrasi Publik, 2015)
Study of village goverment relationship with village conference department in a village regulation construction in Konang Village, Subdistrict Glagah, Lamongan Regency. The relationship between village goverment with village conference department in a Konang village regulation construction based on each duty, right authority, and obligation legally as work partners. This study is conducted to know the mechanism of village regulation construction in Konang village, the relation between village conference department with Konang village goverment in an arrangement of village regulation and a result of village regulation at 2015 that have been arranged and assigned by the village conference department in the partnership with village goverment. Based on the result of the study, the mechanism of regulation arrangement in Konang village is devided into preparation step that includes of planning and preparation, and process that includes of formulation step, discussion, and arrangement technique, and assigned step, invitation, and dissemination. The village conference department with the Konang Headman have good relationship. It happen because the village conference department and Konang village govertment have carried out their each duty and right authority in the village regulation arrangement.The village regulation that have been constructed and assigned by the village conference department with Konang village goverment have been run well. Key words : relationship, village goverment, village conference department, and village regulation.